2008
DOI: 10.1242/jeb.008128
|View full text |Cite
|
Sign up to set email alerts
|

Escaping Flatland: three-dimensional kinematics and hydrodynamics of median fins in fishes

Abstract: SummaryFish swimming has often been simplified into the motions of a two-dimensional slice through the horizontal midline, as though fishes live in a flat world devoid of a third dimension. While fish bodies do undulate primarily horizontally, this motion has important three-dimensional components, and fish fins can move in a complex three-dimensional manner. Recent results suggest that an understanding of the three-dimensional body shape and fin motions is vital for explaining the mechanics of swimming, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…The importance of the third dimension to our understanding of fish propulsion has recently begun to be appreciated [24]; our work now brings a similar three-dimensionality to onboard flow sensing. Here, we used vertically distributed sensors on a three-dimensional craft to examine what is usually studied as a lateral two-dimensional wake, namely the KVS.…”
Section: Geometry Of Craft and Sensor Arraymentioning
confidence: 85%
“…The importance of the third dimension to our understanding of fish propulsion has recently begun to be appreciated [24]; our work now brings a similar three-dimensionality to onboard flow sensing. Here, we used vertically distributed sensors on a three-dimensional craft to examine what is usually studied as a lateral two-dimensional wake, namely the KVS.…”
Section: Geometry Of Craft and Sensor Arraymentioning
confidence: 85%
“…While these techniques have given us a great deal of insight into the fluid mechanics of fish locomotion, the current method of inferring three-dimensional wake structure from repeated two-dimensional PIV slices produces considerable room for error. A mechanism that instantaneously captures a three-dimensional wake structure is needed in order to understand fully the fluid interactions between fishes and their environment, and among the different fins used for propulsion [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Greater wave-like motions and a more downstream-positioned flap during arms-first swimming seemingly contribute to more lift generation, given higher observed lift forces for arms-first compared with tail-first swimming. This is not surprising considering that previous studies on fish and biorobotic systems showed that slight changes in fin behavior and mechanical properties can have a major influence on the timing, direction and magnitude of force production (Tytell et al, 2008;Tangorra et al, 2010;Neveln et al, 2014). Positioning the maximum fin amplitude farther downstream may also help counteract body pitching induced by rear-pointing jets.…”
Section: Fin Motionsmentioning
confidence: 79%